ASSESSING THE IMPACT OF THE RUSSIAN-UKRAINIAN WAR ON THE ACHIEVABILITY OF THE GOALS OF THE SUSTAINABLE DEVELOPMENT ECONOMIC DIMENSION: STRATEGIC ASPECT - Korolchuk, L. V. (The actual problems of regional economy development, 2024)
The article raises the topic of the efficiency of implementing the concept of sustainable development in the current conditions. Today, the issue of the war unleashed by Russia against Ukraine is at the top of the agenda of the world political community. This is a destructive large-scale phenomenon that can affect the economic, social and environmental aspects of public life and, moreover, is classified as a force major, and therefore unpredictable, event. The outbreak of the russian-Ukrainian war could only be assumed as one of the likely scenarios, and therefore this factor was not taken into account in the development of national sustainable development strategies by the UN member states that adopted the final document: “Transforming Our World: The 2030 Agenda for Sustainable Development” back in 2015. If the war has a significant impact on the effectiveness of achieving the Sustainable Development Goals on a global scale, the world’s states should adjust their national strategies for socio-economic development or develop new ones in light of new realities to ensure successful sustainable development. The purpose of the study is to assess the impact of the Russian-Ukrainian war on the achievability of the Sustainable Development Goals globally, and to identify the tasks for each of the selected Goals, the implementation of which is significantly prevented by the war. The study used such scientific methods as analysis and synthesis, induction and deduction, abstraction, forecasting, logical and statistical methods. Based on a study of the literature on this topic, the author identifies the Goals that correlate with the economic dimension of sustainable development. The author analyzes the impact of war on the achievement of the Goals on a global scale, based on reports and statistics on sustainable development from international organizations, as well as on the study of economic literature on the relevant subject. The tasks of the studied Goals, the implementation of which is prevented by the Russian-Ukrainian war, are identified. Based on the conclusions drawn from the study, recommendations are made to improve strategic planning for sustainable development at the state level in the current conditions.